EFEKTIFITAS YOUTUBE SEBAGAI MEDIA DAKWAH (Studi Kasus Akun YouTube Pondok Pesantren Darussalam Blokagung Karangdoro Tegalsari Banyuwangi) - Abdi Fauji Hadiono; Fatma Izzatun Nafi'ah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
This study discusses how the effectiveness of using YouTube as a medium of da'wah for Pondok Pesantren Darussalam Blokagung also discusses how da'wah content is in great demand by the audience and what obstacles are experienced during the process of preaching using YouTube media. The results of this study indicate that the use of YouTube as a Da'wah medium for PondokPesantren Darussalam Blokagung is considered effective because mad'u is able to receive da'wah material delivered through YouTube media, mad'u also causes changes in attitudes and actions after watching da'wah content on the channel. YouTube Darussalam Blokagung. In addition to the effectiveness felt by mad'u, da'wah content which is considered effective according to mad'u is da'wah in the form of live streaming recitations or light lectures. The obstacles in doing da'wah through YouTube are the lack of stable internet network connection, the lack of consistency of the editorial team in uploading content and the long distance between the editorial office and the domicile of the editorial team.